The Influence of Organizational Culture, Organizational Commitment, Job Satisfaction Through Organizational Citizenship Behavior on The Performance of Private School Teachers in Makassar, South Sulawesi - Arifin, St Ardiana (Scientia integritas Utama, 2022)
Creating quality human resources, teachers are at the forefront, because teachers directly deal with students in delivering the learning process. the teacher is one of the human components in the teaching and learning process, which plays a role in efforts to form potential human resources in the field of development. Therefore the teacher who is one of the active and elements in the field of education must play a role in placing his position as a professional, in accordance with the demands of an increasingly developing society. The importance of Organizational Citizen Behavior (OCB) for all forms of organization, because Organizational Citizen Behavior (OCB) can increase organizational effectiveness. All forms of organization will be in dire need of employees who go beyond their job description. One form of organization is educational institutions, namely teachers, therefore this study aims to determine the effect of organizational culture, organizational commitment, job satisfaction through Organizational Citizen Behavior (OCB) on the performance of private school teachers in Makassar, South Sulawesi. This research is quantitative and the data collection method using a questionnaire of 105 samples. Methods of analysis using validation, reliability, analysis, pathways, and hypothesis testing. The results showed that the influence of organizational culture, organizational commitment, job satisfaction through Organizational Citizen Behavior (OCB) had an effect on teacher performance.